2006
DOI: 10.1016/j.jctb.2005.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A map colour theorem for the union of graphs

Abstract: In 1890 Heawood [Map colour theorem, Quart. J. Pure Appl. Math. 24 (1890) 332-338] established an upper bound for the chromatic number of a graph embedded on a surface of Euler genus g 1. This upper bound became known as the Heawood number H (g). Almost a century later, Ringel [Map Color Theorem, Springer, New York, 1974] and Ringel and Youngs [Solution of the Heawood map-coloring problem, Proc. Nat. Acad. Sci. USA 60 (1968) 438-445] proved that the Heawood number H (g) is in fact the maximum chromatic numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The first results about graph coloring deal almost exclusively with planar graphs in the form of the coloring of maps [13]. While working on the map coloring problem of the counties of England, Francis Guthrie postulated the four color conjecture, noting that four colors were sufficient to color a map so that no regions sharing a common border receives the same color.…”
Section: Introductionmentioning
confidence: 99%
“…The first results about graph coloring deal almost exclusively with planar graphs in the form of the coloring of maps [13]. While working on the map coloring problem of the counties of England, Francis Guthrie postulated the four color conjecture, noting that four colors were sufficient to color a map so that no regions sharing a common border receives the same color.…”
Section: Introductionmentioning
confidence: 99%
“…2 and Füredi et al [5] to χ k (K n ) ≤ n + 7 k . Regarding the graphs with bounded genus, let us define χ k (S) to be the maximum of χ k (G) over all graphs G that can be embedded in the surface S. Stiebitz anď Skrekovski [14] have determined the exact values of χ 2 for all surfaces. Füredi et al [5] have shown that…”
Section: Introduction and Definitionsmentioning
confidence: 99%
“…Nordhaus-Gaddum-type theorems establish bounds on f (G) + f (G) for some graph parameter f , where G is the complement of a graph G. The literature has numerous examples; see [1,4,5,8,10,13,14] for a few. Our main result is the following Nordhaus-Gaddum-type theorem for treewidth 1 , which is a graph parameter of particular importance in structural and algorithmic graph theory.…”
mentioning
confidence: 99%